2018
DOI: 10.1074/jbc.ra117.000295
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 2 induces proliferation and fibrosis via SNAI1-mediated activation of CDK2 and ZEB1 in corneal endothelium

Abstract: Investigating stimulation of endogenous wound healing in corneal endothelial cells (CECs) may help address the global shortage of donor corneas by decreasing the number of transplants performed for blindness due to endothelial dysfunction. We previously reported that IL-1β stimulation leads to fibroblast growth factor (FGF2) expression, enhancing migration and proliferation of mammalian CECs. However, FGF2 also promotes the endothelial-mesenchymal transition, which can lead to retrocorneal membrane formation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 53 publications
(83 reference statements)
2
60
0
Order By: Relevance
“…We previously reported that ZEB1 mediates FGF2-dependent fibrosis in the human corneal endothelium ex vivo, 19 and it has also previously reported that SP1 activates expression of type I collagen. 31,32 To investigate the role of SP1 in ZEB1-mediated fibrosis in human corneal endothelium ex vivo, siRNA-mediated ZEB1 knockdown was performed.…”
Section: Fgf2 Induces Sp1 Through Zeb1 In Human Corneal Endothelium Ementioning
confidence: 75%
See 2 more Smart Citations
“…We previously reported that ZEB1 mediates FGF2-dependent fibrosis in the human corneal endothelium ex vivo, 19 and it has also previously reported that SP1 activates expression of type I collagen. 31,32 To investigate the role of SP1 in ZEB1-mediated fibrosis in human corneal endothelium ex vivo, siRNA-mediated ZEB1 knockdown was performed.…”
Section: Fgf2 Induces Sp1 Through Zeb1 In Human Corneal Endothelium Ementioning
confidence: 75%
“…FGF2 induces EnMT as evidenced by changes in cell morphology and expression of mesenchymal transition markers SNAI1 and ZEB1 in human and mouse corneal endothelium. 17,19 SNAI1 serves as a bifurcation point in the regulatory network, below which pathways for regulation of cell proliferation and fibrosis diverge. ZEB1 functions downstream of SNAI1 and promotes fibrosis by activating expression of type I collagen, a major component of retrocorneal membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SDF expression was downregulated in D6 and G4 and 6 undetectable in B3 ( Figure 5C). FGF2, an important growth factor for wound healing, angiogenesis 7 and cellular proliferation 29 was highly upregulated in B3. hCC F1 and D2 increased FGF2 8 expression relative to cCICs and were more reminiscent of MSCs, while hCC D6 and G4 expressed 9 lower levels of FGF2 compared to both parent cells ( Figure 5D).…”
Section: Hb-egf At Levels Intermediate Between the Two Parent Cell Ramentioning
confidence: 99%
“…Among various FGFs, FGF2 and FGF4 are key regulators of EMT during development and cancer progression in the lung [38,39]. It has been reported that FGF2 reduces Ecadherin in human ovarian cancer cells [40], and induces the expression of mesenchymal markers (VIM, FSP1, α-SMA and SNAI1) in corneal endothelial cells [41] and proximal tubular epithelial cells [39,42]. A number of studies have shown the synergistic effect of combined treatment of TGFβ1 and FGF2 in inducing EMT in mouse normal mammary epithelial (NMuMG) cells [43], rat Hertwig's epithelial root sheath (HERS) cells [44], mouse lung epithelial type II cell line MLE-12 [45], human non-small cell lung cancer cell lines NCI-H1975 and NCI-H165 [46], and human lung adenocarcinoma cell lines PC-9, HCC-827 and A549 [47,48].…”
Section: Introductionmentioning
confidence: 99%